Intra- and inter-specific interactions between Coccinella transversalis and Cheilomenes sexmaculata in relation to prey abundance - DAS, R.; DEVEE, A. M. (Journal of Biological Control, 2023)
In the present study, we investigated the feeding rate and the effect of intra- and inter-specific interactions between adults, 3rd and 4th instar larvae of the coccinellids, Coccinella transversalis and Cheilomenes sexmaculata to its conspecific and heterospecific combinations under laboratory conditions. Cannibalism and the effect of interaction were investigated using the multiplicative risk model. Aphidophagous predators and their instars were kept alone, paired with conspecifics, and heterospecifics combinations in the absence and presence of prey (aphid, Aphis gossypii). In the presence of aphids, the combined release of these predator species revealed that except for (3rd × 3rd) and (4th× 4th) intraspecific combination of both predators, the observed consumption was lower than the expected consumption. In the case of interspecific combination, the observed consumption was significantly lower than expected and it indicated the antagonistic effect of both the predators in later instars in the presence of sufficient prey population. In the absence of the prey, intra-specific cannibalism was lowest between adults of both the species and highest among C. transversalis 3rd × C. transversalis adult and C. sexmaculata 3rd × C. sexmaculata adult. The interspecific predation was highest between C. transversalis adult × C. sexmaculata 3rd instar and lowest between adults of both species. The results suggest that C. transversalis was more a successful aphid predator, being able to find aphids more quickly and consume more of them compared to C. sexmaculata. As there was less intraspecific cannibalism among C. transversalis and individual consumption is also high, it is considered to play a significant role as a biocontrol agent in aphid management.